A new lizard malaria parasite Plasmodium intabazwe n. sp. (Apicomplexa: Haemospororida: Plasmodiidae) in the Afromontane Pseudocordylus melanotus (Sauria: Cordylidae) with a review of African saurian malaria parasites. Issue 1 (December 2016) - van As, Johann; Cook, Courtney; Netherlands, Edward; Smit, Nico
Abstract Background Saurian malaria parasites are diverse apicomplexan blood parasites including the family Plasmodiidae Mesnil, 1903, and have been studied since the early 1900s. Currently, at least 27 species ofPlasmodium are recorded in African lizards, and to date only two species, Plasmodium zonuriae (Pienaar, 1962) andPlasmodium cordyli Telford, 1987, have been reported from the African endemic family Cordylidae. This paper presents a description of a new malaria parasite in a cordylid lizard and provides a phylogenetic hypothesis for saurianPlasmodium species from South Africa. Furthermore, it provides a tabular review of thePlasmodium species that to date have been formally described infecting species of African lizards. Methods Blood samples were collected from 77 specimens ofPseudocordylus melanotus (A. Smith, 1838) from Platberg reserve in the Eastern Free State, and two specimens ofCordylus vittifer (Reichenow, 1887) from the Roodewalshoek conservancy in Mpumalanga (South Africa). Blood smears were Giemsa-stained, screened for haematozoa, specifically saurian malaria parasites, parasite stages were photographed and measured. A small volume was also preserved for TEM studies.Plasmodium andHaemoproteus primer sets, with a nested-polymerase chain reaction (PCR) protocol, were employed to target a fragment of the cytochrome-b (cyt-b ) gene region. Resulting sequences of the saurianPlasmodium species' isolates were compared with each other and to other knownPlasmodium spp. sequences in the GenBank database. Results The presence ofP. zonuriae in both specimens of the type lizard hostC. vittifer was confirmed using morphological characteristics, which subsequently allowed for the species' molecular characterisation. Of the 77P. melanotus, 44 were parasitised by aPlasmodium species, which when compared morphologically to other African saurianPlasmodium spp. and molecularly toP. zonuriae, supported its description as a new speciesPlasmodium intabazwe n. sp. Conclusions This is the first morphological and molecular account ofPlasmodium species within the African endemic family Cordylidae from South Africa. The study highlights the need for molecular analysis of other cordylidPlasmodium species within Africa. Future studies should also include elucidating of the life-cycles of these species, thus promoting the use of both morphological and molecular characteristics in species descriptions of saurian malaria parasites.